Philosophical Foundations of Islamic Education Policy: Ontological, Epistemological, and Axiological Perspectives - Zarkoni; Abd. Muis (DAAR EL-IDARAH: Journal of Islamic Education Management, 2025)
This study examines the philosophical foundations of Islamic education policy through ontological, epistemological, and axiological perspectives using a qualitative literature review approach. The review synthesizes peer-reviewed journal articles, academic books, conference proceedings, and research reports relevant to Islamic educational philosophy and educational policy. The analysis involved literature reduction, thematic categorization, conceptual synthesis, and theoretical interpretation to identify major philosophical patterns and research gaps. The findings indicate that ontology provides the Islamic worldview and educational purpose, epistemology integrates revelation, reason, empirical inquiry, and contextual interpretation as legitimate sources of knowledge, while axiology establishes ethical values that guide curriculum development, educational governance, leadership, and policy implementation. The study further reveals that these three philosophical dimensions function as an integrated framework rather than independent concepts, ensuring coherence between educational objectives, knowledge construction, and ethical practice. The proposed framework contributes to the theoretical development of Islamic education policy and offers practical guidance for policymakers in designing philosophically grounded, ethically responsible, and contextually responsive educational policies.